Zakat Mal Distribution at Muhammadiyah and Nahdlatul Ulama Zakat Institutions in Yogyakarta: A Comparative Institutional Study - Masithoh, Masithoh; Kamsi, Kamsi; Asmuni, Asmuni (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2026)
Zakat mal can support poverty alleviation and mustahik empowerment when distribution systems combine religious legitimacy, accurate targeting, accountable governance, and programs suited to beneficiary needs. This study compares the models and implementation of zakat mal distribution by the Muhammadiyah zakat institution (LAZISMU) and the Nahdlatul Ulama zakat institution (LAZISNU) in the Special Region of Yogyakarta during 2019–2023. It employed a qualitative comparative case-study design using interviews with six institutional leaders and staff members, field observations, organizational guidelines, standard operating procedures, distribution reports, and program-achievement records. The evidence was analyzed through within-case interpretation and cross-case comparison across beneficiary classification, consumptive and productive orientation, distribution channels, organizational networks, monitoring, and religious-legal foundations. Both institutions distributed zakat to the eight recognized recipient categories and combined immediate assistance with productive and empowerment-oriented programs. The Muhammadiyah institution used a more formally structured, sector-based program system, while the Nahdlatul Ulama institution relied more visibly on local units, community verification, and embedded religious networks. Their Tarjih and Bahtsul Masail traditions provided interpretive frameworks for legitimizing beneficiaries and programs, but distribution outcomes were also shaped by organizational capacity, regulation, partnerships, and local conditions. Differences in disbursement totals and beneficiary numbers reflected operational scale and reporting systems rather than proven effectiveness. The study contributes an integrated comparative framework linking religious authority, governance, community embeddedness, and distribution practice, while supporting standardized indicators and longitudinal evaluation of mustahik welfare.